Analisis Quality Of Services (QoS) Streaming Video Pada Jaringan Wireless Di Area Sub-Urban (Studi Kasus Desa Kepenuhan Raya, Kabupaten Rokan Hulu) - Wakhidah Rohayati; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Sub-urban area is a residential area located in the suburbs, not far from the city center.Kepenuhan Raya village is one of the sub-urban areas that hasn't used wireless networks for too long. Streaming is a form of technology that allows files to be used directly without waiting for the completion of the upload / download and takes place continuously without interruption. This paper evaluates and analyzes Quality of services (QoS) on wireless networks located in sub-urban areas. Analyzing QoS includes Throughput, Delay / latency, packet loss and bandwidth. The results of the study were taken on workdays and holidays. From these studies the total bandwidth results obtained on workdays with measurements using four PCs is 19.55 Mbps and on holidays that is 18.78 Mbps. In Video Streaming QoS the average value obtained in the morning measurement is 12652588.991 bit/sec Throughput, 0.006 S Delay, and 0% Packet Loss in the morning. With data received as many as 28005431.17 Bytes and delivery time 183.8504 seconds. During the daytime, the Throughput value is 386484.83 Bits / sec, Delay 0.023 S, and Packet Loss 0%. With data received at 9105377.2 Bytes and sending time of 196.839 seconds. At night, the Throughput value is 1141260,380 Bits / sec, Delay 0.005 S, and Packet Loss 0%. With data received at 21232293.8 Bytes and sending time for 182.491 seconds. From these results it can be concluded, the greater the value of the data received, the greater the throughput too. If throughput is large, the smaller the value of Delay and Packet Loss. Keywords: Sub-Urban Area, Wireless, Streaming, QoS